The influence of Test Anxiety on Test scores Among Form one students in Dadaab Refugee Camp, Kenya. - Surum, Janet (IJRDO- Journal of Educational Research, 2016)
The purpose of the study was to determine the relationship between test anxiety and test scores among form ones students in Dadaab Refugee Camp, Kenya. The study was guided by the following two theories: Social cognitive learning by Albert Bandura and Psychoanalytic theory of anxiety by Sigmund Freud. The study adopted a correlational design in order to be able to investigate and analyze the relationship between test anxiety and form one test scores. It also used simple regression to find out whether the various variables would predict test scores. The study wasconducted in four public schools of Dadaab refugee camps in the North-Easternpart of Kenya. The target population consisted of students and teachers. Thesampling technique was that of convenient, purposive and systematic sampling inthat order, where thirty five participants were selected from each school, to sumup to one hundred and thirty eight form one students and a total of thirty fourteachers. Research instruments included questionnaires for teachers and students,while interview schedule was for teachers. The results revealed thattest anxietysignificantly predicted testscores.